TATA KELOLA TEKNOLOGI INFORMASI (IT GOVERNANCE) - Ita Ernala Kaban (Bina Nusantara University, 2009)
Technology advances offer many advantages for information and data storage, delivery, access and processing. Technology advances have also placed information as one of the most prominent resources requiring good and proper management. Information technology management in enterprise, although has been implemented, yet has not been managed using structured approach, thus, it is difficult to measure the roles of Information Technology in supporting business process for achieving enterprise objectives. In that way, the aim of this research is to analyze standard model for IT Governance. From the study, it can be concluded that COBIT has a better compromise in its horizontal and vertical dimension compared to the other standards. COBIT has a wider and more detailed IT process spectrum.Keywords: IT Governance, enterprise, business process